Comparative Evaluation of Bedside Index of Severity in Acute Pancreatitis Bisap) & Modified Computed Tomography Severity Index (MCTSI) in Assessing Severity of Acute Pancreatitis - Rahman Ullah, Mashal Nazir, Farooq Khan, Muhammad Asim Fazal, Nazia Shahana, Asim Khan Yousafzai, Kainat Nazir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare diagnostic accuracy of BISAP and MCTSI in predicting the severity of Acute pancreatitis. Study design: cross sectional study. Setting: Surgical department Khyber Teaching Hospital, Peshawar and Bacha Khan Medical Complex, Swabi. Duration: 6 months Jan, 2021 to June, 2021 Material and Methods: In this study a total of 246 patients were observed. The demographic, clinical and laboratory data of all consecutive patients with a primary diagnosis of AP admitted/transferred to our ward were prospectively collected and then this data were retrospectively analyzed. The day of admission is defined as the first 24hr of hospitalization in our ward or in the referring hospital/ward. Contrast enhanced CT(CECT) and BISAP score were calculated after 72hrs in all patients and they were categorized into three severity grades of Acute pancreatitis based on Atlanta classification 2012 as discussed in operational definition. BISAP score greater than 4 and MCTSI score greater than 8 were considered severe acute pancreatitis. Results: In this study mean age was 45 years with SD ± 16.21. Forty three percent patients were male while 57% patients were female. MCTSI had sensitivity 89.83%, specificity 60%, Positive predictive value was 98.14%, Negative predictive value was 20% and the overall diagnostic accuracy was 88.61%. While BISAP had sensitivity 82.05%, specificity 70%, Positive predictive value was 98.49%, Negative predictive value was 14.89% and the overall diagnostic accuracy was 82.52%. Conclusion: Our study concludes that the diagnostic accuracy of MCTSI is better than BISAP score in predicting the severity of acute pancreatitis. Keywords: MCTSI, BISAP score, severe acute pancreatitis.